Atividade antimicrobiana de extratos de Maclura tinctoria (L) D. Don ex Steud contra patógenos de peixes - Pires, Luana da Costa (2018)
The sanitary conditions to which the animals are submitted in aquaculture are often inadequate, being stressing factors triggering pathological processes as bacterial infections. In this context, bacterial resistance arises through the indiscriminate and misuse of antibiotics, leading in recent years to an increase in the number of antimicrobial resistance. This growth is reflected in aquaculture, where non-responsive pathologies in fish culminate in economic and environmental losses. The large increase in antibiotic resistance and the residual effects of conventional antibiotics stimulates the search for new antimicrobial therapies of low environmental impact that can be used in the prevention and / or treatment of bacterial infections in fish. Looking for this new approach, the tree Maclura tinctoria (Moraceae), contains in its extracts components with recognized antimicrobial properties. The objective of this study was to investigate the in vitro antimicrobial activity of ethanolic extracts of the leaves, bark, sapwood and heartwood of this plant against bacteria of the genus Aeromonas obtained from naturally infected silver catfish (Rhamdia quelen). In addition, we investigated the central depressant activity of the extracts as well as their effects in silver catfish after long exposition, in order to evaluate the safety of a possible therapeutic strategy based on these extracts. In addition, the extract which presented the most promising results in the above- mentioned assays had its effect evaluated in vivo on the survival of silver catfish experimentally infected with A. hydrophila. The in vitro antimicrobial activity was evaluated by the Microdilution method in cation-adjusted-Müller-Hinton broth. The evaluation of the central depressant activity was performed by determining the induction times to the sedative and / or anesthetic state and its subsequent recovery at 30, 100 and 300 mg/L. In the long exposure test the fish were exposed to the concentrations of 30 and 100 mg/L of the extracts for 24 hours. In the in vivo antimicrobial assay, silver catfish were exposed to baths for five days with 30 mg/L of the heartwood extract. The chemical composition of the heartwood extract was analyzed by HPLC-DAD-MS. The heartwood extract showed promising in vitro antimicrobial activity, while the other samples presented weak activity. In the central depressant activity test the leaves extract was the only one to induce a stage of deep sedation, the other extracts induced the light sedation stage in the three analyzed concentrations. The long exposure experiment showed a behavior that ranged from normal to light sedation for the animals submitted to extracts of the bark, sapwood and heartwood, and the leaf extract caused a deepening of the sedation stages. The in vivo antimicrobial assay revealed a high survival rate (85.4%) of the animals exposed to the heartwood extract compared to the untreated control (6.9%) without statistical difference to florfenicol (100%). The chemical composition revealed the presence of compounds of the polyphenol class. Heartwood extract showed to be an alternative for the treatment of bacterial infections caused by A. hydrophila in silver catfish.